THE ASSOCIATION BETWEEN TYPE 1 DIABETES AND CELIAC DISEASE IN CHILDREN - AWAIS, M; RASHEED, AS; SALEEM, MU (Biological and Clinical Sciences Research Journal, 2023)
Type 1 diabetes (T1D) and celiac disease (CD) are common autoimmune diseases that may occur together in children. This research article examined the association between T1D and CD in children through a systematic review and meta-analysis of existing observational studies. A comprehensive literature search was conducted using electronic databases such as MEDLINE, Embase, and Cochrane Library. Studies reporting the prevalence of CD in children with T1D were included in the meta-analysis. The data were extracted, and a random-effects meta-analysis was performed to estimate the pooled prevalence of CD in children with T1D and the odds ratio (OR) for the association between T1D and CD. A total of 26 observational studies, comprising 28,422 children with T1D, were included in the meta-analysis. The pooled prevalence of CD in children with T1D was 6.0% (95% CI: 4.8%-7.3%), significantly higher than the estimated prevalence of CD in the general population. The OR for the association between T1D and CD was 3.81 (95% CI: 2.86-5.08), indicating a statistically significant positive association between the two conditions. This research article concludes a significant positive association between T1D and CD in children. The findings suggest clinicians should consider screening for CD in children with T1D to improve diagnosis and treatment outcomes. Further research is necessary to explore the underlying mechanisms of this association and its implications for clinical practice.